2022
DOI: 10.1111/nan.12793
|View full text |Cite
|
Sign up to set email alerts
|

HnRNP K mislocalisation in neurons of the dentate nucleus is a novel neuropathological feature of neurodegenerative disease and ageing

Abstract: Nuclear depletion and cytoplasmic mislocalisation of the RNA-binding protein heterogeneous ribonucleoprotein K (hnRNP K) within pyramidal neurons of the frontal cortex have been shown to be a common neuropathological feature in frontotemporal lobar degeneration (FTLD) and elderly control brain. Here, we describe a second neuronal subtype vulnerable to mislocalisation within the dentate nucleus of the cerebellum. In contrast to neurons within the cerebellar cortex that typically exhibited normal, nuclear staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…BACE1 levels were higher than controls (table 1), but unlike subtypes 1 and 2, abeta40 levels were similar to controls, suggesting a different mechanism associated with higher BACE1 levels for this subtype. Proteins specifically increased in subtype 3 included heterogenous nuclear ribonucleoproteins (hnRNPs) 70 and other RNA binding proteins, which may point to RNA dysregulation. HNRNPs, are involved in maturation of pre-mRNAs, mRNA stabilisation during transport and local mRNA translation for many RNAs, including those important for cytoskeleton organisation 71,72 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BACE1 levels were higher than controls (table 1), but unlike subtypes 1 and 2, abeta40 levels were similar to controls, suggesting a different mechanism associated with higher BACE1 levels for this subtype. Proteins specifically increased in subtype 3 included heterogenous nuclear ribonucleoproteins (hnRNPs) 70 and other RNA binding proteins, which may point to RNA dysregulation. HNRNPs, are involved in maturation of pre-mRNAs, mRNA stabilisation during transport and local mRNA translation for many RNAs, including those important for cytoskeleton organisation 71,72 .…”
Section: Resultsmentioning
confidence: 99%
“…Disruptions in HnRNPs and mRNA have been associated with tau tangles in previous proteomic studies 73 . Mislocalised hnRNPs could lead to mis-and/or cryptic splicing, resulting in dysfunctional proteins 70,74 . For example, cryptic splicing of STMN2 is a hallmark of TDP43 mislocalisation 75 , resulting in shorter proteins and decreased STMN2 levels in tissue 76 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in both sub-GRNs, the number of TGs that each TF controls varies to an important degree, exhibiting a scale-free like topology. The analysis of the top-10 TFs controlling the highest number of TGs, has revealed that most of these TFs have been found associated to Alzheimer disease in previous studies [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], as reported in Table 4 . The full lists of TFs belonging to both communities are reported in Table A1 .…”
Section: Resultsmentioning
confidence: 93%
“…We put efforts forth in investigating Hnrnpk as a prion modulator, due to its strong effect size, ubiquitous expression (Uhlén et al , 2015 ), and its recent implications in several protein misfolding diseases (Moujalled et al , 2015 ; Bampton et al , 2021 ; Sidhu et al , 2022 ). As Hnrnpk is a cell‐essential gene (Tsherniak et al , 2017 ), we followed several lines of validation in human and mouse cells as well as different modes of genetic perturbation.…”
Section: Discussionmentioning
confidence: 99%